Molecular Engineering - McGee, Henry A. (McGraw Hill, 1991)
Aims to bridge the gap between molecular physics and applied engineering. The book shows how an understanding of matter at the molecular level can lead to creative calculation methods, and solutions outside the scope of traditional engineering, such as laser-based processes for isotope separation.